Quasi-in-situ investigation on recrystallization behavior of an Al–Mg-Sc-Zr alloy under different homogenization processes - Yi Su; Lipeng Ding; Yu Zhang; Chenglin Wang; Yaoyao Weng; Linzhong Zhuang; Zhihong Jia (Journal of Materials Research and Technology)
The influence of different homogenization treatments on the recrystallization behavior of Al–Mg-Sc-Zr alloys during annealing was examined using scanning electron microscopy, transmission electron microscopy and quasi-in-situ electron backscatter diffraction. The results indicate that during the initial annealing period, due to a higher density of Al3(Sc, Zr) dispersoids, the one-step homogenized sample (350 °C/6 h) exhibits superior recrystallization resistance and thus a finer grain distribution compared to the three-step homogenized sample (270 °C/6 h + 350 °C/6 h + 500 °C/8 h). However, with prolonged annealing, the one-step homogenized sample exhibits an accelerated recrystallization rate, resulting in a larger grain size than the three-step homogenized sample. This phenomenon is mainly attributed to the rapid coarsening of Al3(Sc, Zr) dispersoids, which weakens their recrystallization suppression effect and facilitates the preferential growth of S-oriented grains, thereby promoting the grain coarsening. In contrast, the Al3(Sc, Zr) dispersoids in the three-step homogenized sample undergo only slight coarsening, enabling steady growth of the recrystallized grains. Furthermore, the Q orientation serves as the preferred nucleation site for grains after annealing for 5 min. The discovery provides new insights for controlling recrystallization by optimizing second phase particles and annealing processes.